Optimal fractions of phosphorus fertilizer applied in preplanting and in drip fertigation of tomato crop - Marouelli, Waldir Aparecido; Guimaraes, Tadeu Graciolli; Braga, Marcos Brandão; Silva, Washington Luiz de Carvalho e (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to establish the optimal fractions of the total amount of phosphorus to be applied in preplanting and in drip fertigation of determinate‑growth tomato, as well as to determine the effect of the different forms of nutrient application on their soil spatial distribution. Treatments consisted of five schemes of fertilizer application: 100, 75, 50, 25, and 0% of P total dose divided between the pre‑planting (triple superphosphate in band placement) and the fertigation (phosphoric acid). The experiment was carried out in a clayed Oxisol with two P availability classes – 7.5 and 32.9 mg dm-3 (Mehlich‑1). The treatments showed no effect on tomato production variables in the soil with high P availability. However, in the soil with smaller availability of the nutrient, P fertigation showed a quadratic effect on fruit yield, net income, and net rate of return. The best results were obtained with half of the P total dose applied by fertigation. The fertigation allowed P movement in the soil up to 30 cm deep, and horizontal movement up to 15 cm.